Epidemiological impact of public health interventions against diabetes in Qatar: mathematical modeling analyses - Alareeki, Asalah; Awad, Susanne F.; Critchley, Julia A.; El-Nahas, Katie G.; Al-Hamaq, Abdulla O.; Alyafei, Salah A.; Al-Thani, Mohammed H. J.; Abu-Raddad, Laith J. (Frontiers in Public Health, 2023)
Aims: To predict the epidemiological impact of specific, and primarily structural public health interventions that address lifestyle, dietary, and commuting behaviours of Qataris as well as subsidies and legislation to reduce type 2 diabetes mellitus (T2DM) burden among Qataris. Methods: A deterministic population-based mathematical model was used to investigate the impact of public health interventions on the epidemiology of T2DM among Qataris aged 20-79 years, which is the age range typically used by the International Diabetes Federation for adults. The study evaluated the impact of interventions up to 2050, a three-decade time horizon, to allow for the long-term effects of different types of interventions to materialize. The impact of each intervention was evaluated by comparing the predicted T2DM incidence and prevalence with the intervention to a counterfactual scenario without intervention. The model was parametrised using representative data and stratified by sex, age, T2DM risk factors, T2DM status, and intervention status. Results: All intervention scenarios had an appreciable impact on reducing T2DM incidence and prevalence. A lifestyle management intervention approach, specifically applied to those who are categorized as obese and ≥35 years old, averted 9.5% of new T2DM cases by 2050. An active commuting intervention approach, specifically increasing cycling and walking, averted 8.5% of new T2DM cases by 2050. Enhancing consumption of healthy diets including fruits and vegetables, specifically a workplace intervention involving dietary modifications and an educational intervention, averted 23.2% of new T2DM cases by 2050. A subsidy and legislative intervention approach, implementing subsidies on fruits and vegetables and taxation on sugar-sweetened beverages, averted 7.4% of new T2DM cases by 2050. A least to most optimistic combination of interventions averted 22.8%-46.9% of new T2DM cases by 2050, respectively. Conclusions: Implementation of a combination of structural public health interventions is powerful at preventing T2DM onset and slow the T2DM epidemic in Qatar.